2004
DOI: 10.1055/s-2003-814865
|View full text |Cite
|
Sign up to set email alerts
|

Tränen im Krankenhaus - eine Bestandsaufnahme unter Ärzten, Pflegepersonal und Medizinstudenten

Abstract: A questionnaire was used to investigate the crying behavior of medical personnel and medical students in Austrian hospitals. The results from 275 respondents show that shedding tears occurs relatively frequently. Main reasons were dying patients and having to give bad news. Explicitly negative reactions are rare. Attitudes towards crying are generally tolerant, although physicians tend to be more restrictive/(reserved?).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
6
1
Order By: Relevance
“…Compared with the dearth of empirical studies on professionals' tears in psychological literature, medical professionals have published multiple surveys, one case study, and several "op-ed" news pieces on crying behaviors of medical care providers (Barth, Egger, Hladschik-Kermer, & Kropiunigg, 2004;Blankenship, 1984;Krauser, 1989;Kukulu, 2006;Lerner, 2008;Majhail & Warlick, 2011;Sinclair, 2011;Sung et al, 2009;Wagner, Hexel, Bauer, & Kropiunigg, 1997). It is striking that, as a profession that so explicitly values emotions and interpersonal interaction, psychologists have attended less to the topic of tears than medical professionals.…”
mentioning
confidence: 99%
“…Compared with the dearth of empirical studies on professionals' tears in psychological literature, medical professionals have published multiple surveys, one case study, and several "op-ed" news pieces on crying behaviors of medical care providers (Barth, Egger, Hladschik-Kermer, & Kropiunigg, 2004;Blankenship, 1984;Krauser, 1989;Kukulu, 2006;Lerner, 2008;Majhail & Warlick, 2011;Sinclair, 2011;Sung et al, 2009;Wagner, Hexel, Bauer, & Kropiunigg, 1997). It is striking that, as a profession that so explicitly values emotions and interpersonal interaction, psychologists have attended less to the topic of tears than medical professionals.…”
mentioning
confidence: 99%
“…Fewer than a handful of empirical studies have examined the experiences with and attitudes towards crying among physicians and/or medical interns. To the best of our knowledge, only Barth, Egger, Hladschik-Kermer, and Kropiunigg (2004) and Wagner, Hexel, Bauer, and Kropiunigg (1997) examined the occurrence of crying among physicians and medical interns in hospitals. Both studies showed that the majority of physicians (respectively 57% and 53.1%) and medical interns (respectively 31% and 37.9%) had ever cried in the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Angoff (2001), Kukulu and Keser (2006) and Sung et al (2009) additionally focussed specifically on the crying of medical interns during their internships. Remarkably, these studies among medical interns yielded substantially more variation in the findings (ranging between 31% and 73%) (Angoff, 2001; Barth et al, 2004; Kukulu & Keser, 2006; Sung et al, 2009; Wagner et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations